(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Lepidoptera Noctuidae has been monitored in the Po Valley (Northem Italy) during an eight year period (1989-1996). Pheromone traps of different shapes and light traps have been used. Pheromone traps have been checked 12 months every year. The list of the caught species is given. A comparison between the data collected in the area under investigation and the surrounding ones has been performed. Among the species found, some have never been reported in the area: Aletia impura (Hiibner), Ctenoplusia accentifera (Lefebvre), Spaelotis ravida (Denis & Schiffermiiller), Xestia sexstrigata (Haworth) and Meganephria bimaculosa (Linné).